Individualized medical treatment options in Cushing disease - Gilis-Januszewska, Aleksandra; Bogusławska, Anna; Rzepka, Ewelina; Ziaja, Witold; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2022)
Cushing disease (CD) is caused by a pituitary tumor which oversecretes adrenocorticotropic hormone (ACTH). It is a serious endocrine disease associated with increased mortality and impaired quality of life. The management of CD remains challenging. Although transsphenoidal surgery is the treatment of choice in most cases, in approximately half of CD patients, second or third-line treatment options are needed. Currently, new medical therapies are available which target adrenal steroidogenesis, pituitary somatostatin and dopamine receptors, and glucocorticoid receptors. Selection of which medication to use should be individualized and is determined by many factors including severity of the disease, possible side effects, patients preferences and local availability. The aim of this article is to describe currently available medical therapy to help clinicians individualize the treatment options in the context of recently updated Pituitary Society recommendations.